Recent bird observations from the Banggai Islands - Indrawan, M; Masala, Y; Pesik, L (KUKILA, 1997)
Together with the neighbouring Sula Islands, the Banggai Island group is considered by BirdLife International as an important endemic bird area (ICBP 1992; Sujatnika et al. 1996), because it holds as many as nine restricted range species. Though the two island groups have been assigned a critical conservation priority (ICBP 1992), their fauna remains little known (White & Bruce 1986; Bishop 1992). Intensive coverage for the Sula Islands was completed only in 1991 (Davidson et al. 1994). During a contemporary expedition to study the status of Sula Scrubfowl Megapodius bemsteinii from 9 October to 9 December 1991 in the Banggai Islands, we recorded incidental observations on other species. This report aims to contribute to the present knowledge of distribution and biology of the birds of the Banggai Islands with emphasis on restricted range and little known species and the provision of new island records Where pertinent, observations from Sidangori Batui in eastern Sulawesi, made by MID two days in September 1991, are referred to in the species accounts. Observations during an additional excursion to the Banggai Islands on 31 August 1996 (MID) are also incorporated.